Comparison of the dietary habits of elite Turkish male and female weightlifters - Sener, O. A.; Güner, A. (Journal of Education and Training Studies, 2017)
Nutritional habits affect performance directly or indirectly in weight class included sports. The aim of this study was to compare the dietary habits of elite female and male weightlifters. After getting official records of athletes from Turkish Weightlifting Federation, a survey was conducted on several factors of the athletes such as weight class, education level, national and international success, income level, weight reduction condition, whether the athlete has knowledge about nutrition, fluid intake, dietary approach before competitions, and type of ergogenic usage. The correlation analyses were completed to determine the relationship between the groups. One-way ANOVA was used to compare the groups. Fischer`s exact tests were calculated again to compare the dietary preferences between different groups. Results of this study showed that lower income, weight category, lower age and level of education of male weightlifters negatively affect the performance. Male weightlifters underestimate the importance of fluid intake and they consumed different types of diets. The use of ergogenic products in female weightlifters was differentiated according to their education levels, weight classes and the competition category. Again, the international female weightlifters consumed more ergogenic substance than national level weightlifters. Both male and female weightlifters showed no significant correlations between the performance variables and all other conditions. It can be suggested that the socio-economic status and education level related to sport nutrition in weightlifters should be increased for enhancing of the weightlifting performance.